Les sonnets de Shakespeare revus et corrigés par le XIXe siècle français - Isabelle Schwartz-Gastine (Revue LISA)
In 20th century France the most popular translation of Shakespeare’s sonnets was the volume published in 1955 by the poet Pierre-Jean Jouve who claimed this “poetic prose” as his personal creation. But in fact, the first translations came out in prose too, and at a very late date, that is at the beginning of the 19th century. Shakespeare’s sonnets being first considered as the fruit of an immature pen, the initial translators took upon themselves to improve the originals. Prose was used as a Romantic gesture of defiance against the established rules (Amédée Pichot, 1821 and François-René de Chateaubriand, 1836); but verse was also used, although the original pattern was discarded in favour of the Italian or French one (i.e. two quatrains and two tercets), and the lines were alexandrines (Léon de Wailly, 1834 and Ernest Lafond, 1856). In 1857, François-Victor Hugo announced his volume as the first translation of the whole sequence. Hugo’s prose aimed at a closer rendering; nevertheless he was much influenced by the Romantic spirit and believed in an autobiographical source of inspiration. But whatever their choice, verse or prose, the translators found it necessary to alter the original dramatically to suit French taste. One woman only ventured a small selection (Simone Arnaud, 1891). The first 19th-century translations paved the way for an extreme variety of further renderings, and there is still scope for more, even on the eve of the 400th anniversary of the original publication by Thomas Thorpe in 1609.